Withania somnifera in Neurological Disorders: Ethnopharmacological Evidence, Mechanism of Action and its Progress in Delivery Systems - Syed, Anees A.; Reza, Mohammad I.; Singh, Pragati; Thombre, Ganesh K.; Gayen, Jiaur R. (Current Drug Metabolism, 2021)
Background: The underlying cause of major neurodegenerative disorders remains a healthcare mystery. The thoroughly investigated causes include oxidative stress, inflammation, environmental factor, mitochondrial dysfunction, and irregular neuronal protein aggregation. Withania somnifera has been used for more than 2500 years as a useful medicinal plant to improve disease defense, prevent aging, rejuvenate the body in a vulnerable situation, and generate a feeling of mental well-being. However, a persuasive paper emphasizing its neuroprotective nature is missing. Objective: In the current review, we have delineated the protective role of W. somnifera against various neurological disorders and its progress in delivery systems. Methods: The database used in the retrieval of data were PubMed, Scopus, Science direct, and SciFinder. The keywords used were W. somnifera, Ashwagandha, neuroprotective activities, etc. The principal source of the data retrieval includes research articles, review papers, and short communications from reputed publishers, including the New England Journal of Medicine, Elsevier, Nature, Springer, and Taylor & Francis. Results: After an extensive literature review, we found that W. somnifera mitigates various neurological disorders, including Parkinson's disease, Alzheimer's disease, Huntington disease, tardive dyskinesia, stroke, and anxiety. Furthermore, natural compounds in nano sizes range possess better neuroprotective activity. Consequently, polymeric nanomicelles, nanoparticles, and nanofibers of natural products are used in the treatment of neurodegenerative diseases. Conclusion: The current review substantially deciphered the protective role of W. somnifera against various neurological disorders. However, future studies are further required better to understand the molecular mechanisms behind their neuroprotective nature.
Keywords: Ashwagandha